3/(x²+x -6) =a/(x+3) +b(x-2);
3/(x²+x -6) =(ax -2a+bx+3b)/(x+3) (x-2 );
3/(x²+x -6) =((a+b)x +3b -2a)/(x²+x -6) ;
3= (a+b)x +3b -2a;
{ a+b =0 ; 3b -2a=3.⇒{b = - a; a= - 3/5 ;
a= - 3/5 ; b =3/5
____________________
3/(x²+x -6) =3/(x-2)(x+3) = (-3/5)* ((x-2) -(x+3)) /(x-2)(x+3) =
(-3/5)* ( (x-2)/(x-2)/x+3) - (x+3)/(x-2)(x+3) ) = (-3/5)/(x+3) +(3/5)/(x-2)
____________________
Докажите, что если , то верны следующие производные пропорции:
+- (это плюс минус сразу)
/ - это дробь
а) a+-b/a = c+-d/c правильно: (a±b)/a =(c±d)/c .
б) a+-c/b+-d=a/b=c/d ;
в) a+b/a-b=c+d/c-d
г) a/b=na+mc/nb+md a/b= (na+mc)/(nb +md) .
⇒ b/a = d/c;
a) ⇒ b/a = d/c.
1+b/a= 1+ d/c⇔(a+b)/a =(c+d)/c ;
b/a = d/c⇔- b/a = -d/c⇔1 -b/a =1 -d/c⇔(a-b)/a =(c-d)/c.
(a±b)/a =(c±d)/c.
г) ⇔na/nb =mc/md ⇒na/mc =nb/md ⇔na/mc +1 =nb/md +1⇔
(na+mc)/mc =(nb +md)/md ⇔(na+mc)/c =(nb +md)/d⇔(na+mc)/(nb +md) = c/d =a/b.